Vermicompost Influences Processing Quality Of Potato Tubers (SAARC Journal of Agriculture, 2020)
The effect of vermicompost on dry matter and specific gravity of potato tubers under ambient storage condition was studied. Vermicompost was used at four rates viz. 0, 2, 4 and 6 t ha-1 over the four varieties of potato viz. BARI TPS-1, BARI Alu-28 (Lady Rosetta), BARI Alu-25 (Asterix) and BARI Alu-29 (Courage). Results demonstrated that processing parameters such as dry matter percentage (%) and specific gravity increased with increasing vermicompost levels while they decreased with the increasing storing period. Lady Rosetta and Asterix potato varieties can be safely stored at normal room temperature up to 60 days. There was no interaction between vermicompost rates and crop varieties. Hence, the potato growers of Bangladesh can use vermicompost at 6 t ha-1 for achieving better yield without affecting processing quality.SAARC J. Agri., 17(2): 173-184 (2019)